Comparative study on in vivo response of porous calcium carbonate composite ceramic and biphasic calcium phosphate ceramic - He, Fupo; Ren, Weiwei; Tian, Xiumei; Liu, Wei; Wu, Shanghua; Chen, Xiaoming (Materials Science & Engineering C, 2016)
In a previous study, robust calcium carbonate composite ceramics (CC/PG) were prepared by using phosphate-based glass (PG) as an additive, which showed good cell response. In the present study the in vivo response of porous CC/PG was compared to that of porous biphasic calcium phosphate ceramics (BCP), using a rabbit femoral critical-size grafting model. The materials degradation and bone formation processes were evaluated by general observation, X-ray radiography, micro-computed tomography, and histological examination. The results demonstrated excellent biocompatibility and osteoconductivity, and progressive degradation of CC/PG and BCP. Although the in vitro degradation rate of CC/PG was distinctly faster than that of BCP, at 4week post-implantation, the bone generation and material degradation of CC/PG were less than those of BCP. Nevertheless, at postoperative week 8, the increment of bone formation and material degradation of CC/PG was pronouncedly larger than that of BCP. These results show that CC/PG is a potential resorbable bone graft aside from the traditional synthetic ones. [Display omitted] •A calcium carbonate composite ceramic (CC/PG) was acquired.•The in vivo response of CC/PG and biphasic calcium phosphate (BCP) was compared.•CC/PG showed faster in vitro degradation rate compared to BCP.•CC/PG showed less in vivo degradation and bone formation than BCP at week 4.•CC/PG had larger increment of degradation and bone formation than BCP at week 8.